Perfusion alters stiffness of deep gray matter - Hetzer, Stefan; Birr, Patric; Fehlner, Andreas; Hirsch, Sebastian; Dittmann, Florian; Barnhill, Eric; Braun, Juergen; Sack, Ingolf (Journal of Cerebral Blood Flow and Metabolism, 2018)
Viscoelastic properties of the brain reflect tissue architecture at multiple length scales. However, little is known about the relation between vital tissue functions, such as perfusion, and the macroscopic mechanical properties of cerebral tissue. In this study, arterial spin labelling is paired with magnetic resonance elastography to investigate the relationship between tissue stiffness and cerebral blood flow (CBF) in the in vivo human brain. The viscoelastic modulus, |G*|, and CBF were studied in deep gray matter (DGM) of 14 healthy male volunteers in the following sub-regions: putamen, nucleus accumbens, hippocampus, thalamus, globus pallidus, and amygdala. CBF was further normalized by vessel area data to obtain the flux rate q which is proportional to the perfusion pressure gradient. The striatum (represented by putamen and nucleus accumbens) was distinct from the other DGM regions by displaying markedly higher stiffness and perfusion values. q was a predictive marker for DGM stiffness as analyzed by linear regression |G*| = q·(4.2 ± 0.6)kPa·s + (0.80 ± 0.06)kPa (R2= 0.92, P = 0.006). These results suggest a high sensitivity of MRE in DGM to perfusion pressure. The distinct mechano-vascular properties of striatum tissue, as compared to the rest of DGM, may reflect elevated perfusion pressure, which could explain the well-known susceptibility of the putamen to hemorrhages.
CRIS-Team Scopus Importer:2022-08-03
Keywords: ASL; Deep gray matter; elasticity; mechanical properties; MRE; perfusion